Human Dignity in the Criminal Process: A Lesson Learned from Torture Case in Germany - Prahassacitta, Vidya (Indonesian Comparative Law Review, 2023)
The research aims to analyze the prevising human dignity in the criminal process, especially in cases regarding torture for good purposes.  In the interrogation process, the preparator does not give any information about the hostage; at the same time, the hostage’s condition becomes critical.  Does harm given to the preparator without causing injuries within a short time to save a hostage be accepted and not violate human dignity? The researcher conducts document research and applies a comparative law approach to answer the question. The study compares Indonesian and German legal systems to show the different perspectives on the issue. The research shows that historical and cultural dimensions shape the concept of human dignity in each legal system, and it has a consequence with the idea of proportionally deterring torture for good purpose action. Under Germany's legal system, this action cannot be accepted because human dignity is the supreme value of the Constitution. It is a bit different from the Indonesian legal system, where the concept of human dignity shall maintain a balance between individual and community rights; the action might be accepted with strict requirements.